Tumor biomarker testing in non-small-cell lung cancer: A decade of change. (February 2018) - VanderLaan, Paul A.; Rangachari, Deepa; Majid, Adnan; Parikh, Mihir S.; Gangadharan, Sidharta P.; Kent, Michael S.; McDonald, Danielle C.; Huberman, Mark S.; Kobayashi, Susumu S.; Costa, Daniel B.
Highlights: Review of biomarker testing on over 1000 patients with non-small cell lung cancer. Biomarker testing patterns evolve with approval of new targeted therapies. Smoking status affects the frequency of targetable oncogenic drivers. Abstract: Introduction: Although a growing list of essential genomic/immune-based biomarkers are linked to approved non-small-cell lung cancer (NSCLC) therapies worldwide, few reports have detailed the evolution of NSCLC predictive biomarker assessment in routine clinical practice. Methods: We retrospectively reviewed the first one thousand plus NSCLC patient specimens from our institution analyzed for predictive biomarkers from 2004 to 2017 and evaluated patterns of testing as well as correlation with clinical-pathologic characteristics. Results: The majority of 1009 NSCLC patients had advanced stages of adenocarcinoma with most tissues obtained from the lung, mediastinal/hilar nodes, or pleura. The majority of testing was performed on cytology or small biopsy specimens. All were tested for EGFR mutations, 895 for ALK rearrangement, 841 for KRAS mutation, 537 for ROS1 rearrangement, and 179 using comprehensive genomic profiling. Implementation of near-universal genomic biomarker testing at our institution for EGFR, ALK, ROS1 and PD-L1 all occurred within the first year following evidence of clinical activity or regulatory body approval of an associated inhibitor. The overall testing failure rate after use of the best specimen for the most common tests was ≤5.5%. A quarter of tumors had a driver oncogene identified ( EGFR / ALK / ROS1 / BRAF V600E) with an approved oral targeted therapy, with the highest prevalence in those patients with no or light (≤15 pack-years) history of tobacco use. Conclusions: Tumor biomarker testing using clinical NSCLC specimens in routine oncologic care evolves rapidly following approval of targeted therapies linked to diagnostic assays. Our practice's decade plus experience highlights the rapid evolution of biomarker testing and confirms the therapeutic relevance of such testing in all patients—particularly those patients with light/no history of tobacco use.